Efektivitas Penggunaan E-LAPD Berorientasi Problem Based Learning untuk Meningkatkan Keterampilan Metakognitif pada Materi Kesetimbangan Kimia - Yulia Rahmawati Zain; Rusly Hidayah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the effectiveness of using Problem Based Learning (PBL) oriented E-LAPD to improve students' metacognitive skills on chemical equilibrium material, especially on the sub-material of factors that influence chemical equilibrium shifts. This study was conducted at SMAS Hang Tuah 4 Surabaya class XII-2 as many as 25 students. The type of research used is research and development (R&D) with a 4-D model that was tested on a limited basis using a one-group pretest-posttest design. Scoring on the pretest-posttest uses N-gain (normalized gain) which aims to determine the increase in metacognitive skills through the results of students' pretest-posttest scores. The results showed that the N-gain value for each component of metacognitive skills, namely planning skills, monitoring skills, and evaluating skills, obtained values ​​​​sequentially, namely 0.85; 0.73; and 0.74 which are included in the high category, from the assessment shows that the use of PBL oriented E-LAPD is declared effective in improving students' metacognitive skills. This is supported by the results of the Metacognitive Awareness Inventory (MAI) questionnaire, which showed a percentage of planning skills of 82.43% with very good criteria, monitoring skills of 81.86% with very good criteria, and evaluating skills of 77.67% with good criteria. These results indicate that the MAI questionnaire can support pretest-posttest data to determine the improvement of metacognitive skills in students.